Notes on the Description of Novel Prokaryotic Taxa - Teo, Wee Fei Aaron; Mondotte, Juan A.; Liu, Jia; Ay, Hilal; Brandao, Marcelo Luiz Lima; Cai, Man; Etchebehere, Claudia; Li, Wen-Jun; Pathom-Aree, Wasu; Sawabe, Tomoo; Seo, Taegun (SPRINGER, 2026)
Accurate and reproducible descriptions of novel prokaryotic taxa are essential for understanding their evolutionary relationships and ecological roles. This editorial review provides detailed guidelines for standardizing the description of novel taxa, in alignment with the International Code of Nomenclature of Prokaryotes (ICNP). The recommendations focus on essential requirements for documentation, designation, and nomenclature of prokaryotic taxa. This structured approach supports researchers in producing consistent, well-defined descriptions that meet current standards for valid publication and effective classification of novel prokaryotic taxa.
Keywords: TAXONOMY; Microbiology